Implementasi Pembelajaran Berbasis Science, Technology, Engenering, Art And Mathematich (STEAM) untuk Meningkatkan Kompetensi Paedagogik dan Professional Guru SD Melalui Metode Lesson Study - Idam Ragil WA, Hadi Mulyono Roy Ardiansyah, Dwi Yuniasih Saputri Fadil Purnama Adi (Jurnal Pendidikan Dasar, 2020)
Abstract. The purpose of this service is to train elementary school teachers to implement Science, Technology, Engineering, Art and Mathematich (STEAM) Based Learning. In addition to training teachers, this service also aims to analyze the pedagogical and professional competences of elementary school teachers through the lesson study method in Surakarta. The subjects of this service are elementary school teachers in the city of Surakarta. The method used in this service starts with Workshop, Practice, and Implementation. In conducting this training, the subjects were asked to take tests related to implementing Science, Technology, Engineering, Art and Mathematics (STEAM) Learning. The data analysis used was pre-test and post-test. The result of this activity is that there is an increase in the knowledge and understanding of teachers implementing Science, Technology, Engineering, Artand Mathematich (STEAM) Learning in Elementary School Teachers in Surakarta.Keywords: STEAM, Pedagogic, Professional, Teacher Competence